A justiça restaurativa como via de tutela penal nos impasses de conjugalidade violenta em face das implicações criminais da Lei 11.340/2006 : (im)possibilidades e desafios - Silva, Wirna Maria Alves da (2022)
Violence against women, a remote practice and very present in society, gives rise to the feeling of fear and insecurity, becoming a serious problem that crosses the social layer, and in the country's penal system, the main dialectic to deal with the criminality panorama is through punishment, aspects that lead to criminal justice. Our study seeks to investigate the practices carried out in the Brazilian judiciary, and then answer: “Is it appropriate to use Restorative Justice in cases of violent conjugality in the face of the criminal implications of Law No. 11.340/2006 and in this perspective, what is the paradigm of justice that guides such practices within the scope of special courts of domestic and family violence against women for the recognition of the victim as a subject of law, based on female citizenship?” The thesis raises a comparison between two forms of justice while discussing the need to overcome the monological response of the jurisdictional model, based on the neutralization of the victim and its consequent expropriation of the conflict by the State. This concern is combined with the examination of the risks of articulation between two different rationales, which directly reflect on the subjects: victim/aggressor/community and the need to collaborate with other sectors in order to obtain agreements and the probability of results, emphasizing the JR, while possible, as a booster of the transition from the paradigm of guilt to that of responsibility. We will use a qualitative approach method, examining studies and reports and documents that combine JR and domestic and family violence against women. The hypothesis to conduct the investigation is based on the consonance with the processes of social and cultural change through educational and reflective means in a welcoming space, with the aim of sheltering needs in order to provide: overcoming, security and autonomy, but, for that it is necessary to understand the challenges and potentialities in the national legal system.